Cu(I)-catalyzed cycloaddition of constrained azido-alkynes: access to 12- to 17-membered monomeric triazolophanes incorporating furanoside rings - Ray, A.; Manoj, Kochunnoonny; Bhadbhade, Mohan M.; Mukhopadhyay, R.; Bhattacharjya, A. (Tetrahedron Letters, 2006)
A strained monomeric 12-membered triazolophane was formed by the Cu(I)-catalyzed intramolecular cycloaddition of an azide to an alkyne having a constrained tether incorporating ail aromatic ring and a furanoside ring. Similar cycloadditions of azido-alkynes having ester, furanoside and peptidic tethers led to the formation of monomeric triazolophanes of higher ring sizes. (c) 2006 Elsevier Ltd. All rights reserved.

Conformational polymorphism in racemic 2,4-Di-o-Benzoyl-6-o-Tosyl myo-Inositol 1,3,5-Orthoacetate - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Journal of Structural Chemistry, 2010)
The title compound, C(29)H(26)O(10)S, yields two conformational polymorphs concomitantly from dichloromethane-methanol mixture; the major polymorph grows as plates (Form I, monoclinic, P2(1)/n) and the minor polymorph grows as needles (Form II, triclinic, P-1). The two forms differ mainly in orientation of the tosyl group. In Form I, sulfonyl oxygen of the tosyl group makes intermolecular C -HaEuro broken vertical bar O interactions, whereas the same group in Form II is involved in an intramolecular short dipolar S=OaEuro broken vertical bar C=O (sulfonyl-carbonyl) contact. The molecular organization and the influence of various weak non-covalent interactions that stabilize these conformers in the crystal lattices are discussed.
Keywords: Conformation; crystal structure; dipolar interactions; Inositol; non-covalent interactions; polymorphism; sulfonyl-carbonyl contact

Crystal structure analysis of highly efficient chiral resolution of (RS)-arginine-fumaric acid cocrystal under preferential enrichment conditions - Manoj, Kochunnoonny; Takahashi, Hiroki; Iwama, Sekai; Gonnade, G. Rajesh; Tsue, Hirohito; Tamura, Rui (Journal of Molecular Structure, 2021)
Two new hydrate cocrystals, (RS)-arginine-fumaric acid-H2O ( 2 ) and (S)-arginine-2 fumaric acid-H2O ( 3 ), were obtained by the slow evaporation of the saturated aqueous ethanol solution of a 1:1 mixture of S-enriched arginine (33% ee) and fumaric acid or (S)-arginine and fumaric acid, respectively. Cocrystals 2 and 3 possess an isostructural molecular organization containing homochiral 1D chains of arginine sim-ilar to that of the anhydrous cocrystal of (RS)-arginine-fumaric acid ( 1 ). The latter showed an efficient ``preferential enrichment (PE)'', a unique spontaneous enantiomeric resolution phenomenon by simple recrystallization from the highly supersaturated solution. The formation of unstable cocrystals 2 and 3 seems to have played a crucial role in the enrichment of arginine in the mother liquor under PE crystal-lization conditions. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Arginine; cocrystals; crystal structure; Enantiomeric resolution; preferential enrichment

Cocrystal approach to modulate the photoluminescent properties of a GFP chromophore analogue: role of halogen/hydrogen bonding in achieving a wide range of solid-state fluorescence emissions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Annadhasan, Mari; Biswas, Anupam; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (Crystal Growth & Design, 2023)
Fine-tuning the photophysical properties of fluorescentorganicsolids is essential to attain multicolor displays and meet the demandfor futuristic light-emitting materials. Here, we report the tunableluminescence of a green fluorescent protein (GFP) chromophore analogue,3,4,5-TIA (A), based on the formation of two-component molecular cocrystalswith six different coformers. Coformers selected to synthesize thebinary cocrystals include 1,4-diiodotetrafluorobenzene (B), perfluoronaphthalene(C), 1,4-dibromotetrafluorobenzene (D), 2,3,5,6-tetrafluoroterephthalicacid (E), benzene-1,2,4,5-tetracarbonitrile (F), and benzene-1,2,4,5-tetracarboxylicacid (G). Interestingly, the cocrystals A center dot C and A center dot Fshowed molecular crystal polymorphism with a slight variation in fluorescence,revealing an aggregation-induced emission (AIE). A crystal structureanalysis showed the interplay of hydrogen bonding, halogen bonding,and aromatic pi-stacking interactions in associating neutralsolid components in the cocrystal. All of the novel cocrystals displayeda wide range of photoluminescence ranging from blue to dark orange.The time-dependent density functional theory (TD-DFT) calculationsindicate the changes in the energy level structures (HOMO to LUMO)in cocrystals that resulted in variations in fluorescence emission.The study aims to further understand the structure-propertyrelationship between molecular arrangement and photoluminescence. Cocrystals of a GFPc analogue with differentcoformers displayeda wide range of fluorescence emissions ranging from blue to dark orangewith varying quantum yields. With similar geometries of pi-stackinginteractions, hydrogen and halogen bonding have played a vital rolein fine-tuning the photoluminescence; halogen bonding leads to a blueshift, and hydrogen bonding results in a red shift.